2022
DOI: 10.1177/11786302221117071
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers’ Compliance With Standard Precautions and Associated Factors in Bahir Dar Town, Ethiopia

Abstract: Background: According to the literature analysis, the majority of the studies focused primarily on public health institutions. Although assessing the compliance of healthcare workers in private and public institutions would give comprehensive evidence on existing problems and appropriate prevention method, as a result, research on adherence to standard precautions are still required. Rely on existing research, to the best of the investigator’s knowledge, compliance with standard precautions in hospitals of Bah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 16 publications
3
10
2
1
Order By: Relevance
“…A constant running water supply in the working area might directly promote compliance with standard precaution practices among HCWs because access to poor or interrupted water supply can hamper infection prevention practices in healthcare facilities. This association is consistent with the earlier studies done in Bahir Dar, Ethiopia ( 29 ), Hawassa, Ethiopia ( 31 ), Addis Ababa, Ethiopia ( 40 ) and Nigeria ( 33 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A constant running water supply in the working area might directly promote compliance with standard precaution practices among HCWs because access to poor or interrupted water supply can hamper infection prevention practices in healthcare facilities. This association is consistent with the earlier studies done in Bahir Dar, Ethiopia ( 29 ), Hawassa, Ethiopia ( 31 ), Addis Ababa, Ethiopia ( 40 ) and Nigeria ( 33 ).…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study were, however, less favorable than those of studies carried out in Bahir Dar Town (41%) (29), Dawuro Zone, southwest Ethiopia (65%) (30), Hawassa Comprehensive Hospital, Sidama Ethiopia (56.5%) (31), North Shewa, Oromia (46.8%) (21), Addis Ababa, Ethiopia (66.1%), public hospitals in Abuja, Nigeria (76.2%) (32), and other two tertiary hospitals in Nigeria (50.8%) (33). The magnitude of compliance with standard precaution practice and knowledge among healthcare workers in public hospitals of South Wollo zone, northeastern Ethiopia, April-May 2021 (n = 1,100).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Some of the studies conducted in the aforementioned health facilities had included HCWs in health centers as study participants in addition to hospital health workers. 6 , 10 , 22 Another study included non-health professionals as data participants. 24 In addition, one study used a measurement mechanism for dependent variables that differed from our study.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In Ethiopia, only about half of the HCWs practiced appropriate standard precautions. [9][10][11] The studies identified the associated factors for the poor compliance of the HCWs to the SPs, including lack of infection control programs, lack of training, lack of knowledge and negative attitude towards SPs, inadequate management support, lack of supplies, crowded hospitals and excessive workloads. [12][13][14] Different initiatives were set globally and nationally to improve the wellbeing of patients, visitors, attendants, support staff, HCWs and general community in health care facilities, including Clean Care is Safer Care (WHO) and Ethiopian hospitals reform implementation guidelines (EHRG) aiming to improve quality of service and Clean and Safe Hospitals (CASH) aiming to make hospitals a clean, comfortable and safe environment for HCWs by Ethiopian government.…”
Section: Introductionmentioning
confidence: 99%